Root cause failure analysis of a tracked vehicle balance arm. (October 2017) - Khan, Ayaz M.; Mahmood, Khalid; Waheed ul Haq, Syed; Choudhry, Rizwan Saeed; Khan, Shahbaz Mahmood
Highlights: Failed Tracked vehicle balance arm analyzed using NDT and Fractography. Failure initiated with multiple cracks from spline teeth near the internal diameter. Fracture was of brittle nature and occurred due to Manufacturing Fault i.e. MnS inclusions. Loading condition, failure mode and state of stress determined. Abstract: This paper relates to an upgraded Industrial tracked vehicle which was found with a failed Balance arm during disassembly. The failure analysis of an actual Balance Arms surface was carried out using Fractography and Non Destructive testing techniques to dig out the root cause. The analysis revealed microscopic signatures categorically pointing towards post failure surface mechanical damage. The factor causing to promote failure was improper manufacturing i.e. casting which was further attributed to MnS inclusions.